The long-run impact of historical shocks on the decision to migrate: Evidence from the Irish Migration - Gaia Narciso; Battista Severgnini; Gayane Vardanyan (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
What is the long-run impact of large negative historical events on the individual decision to migrate? We investigate this research question by looking at the effect of the Great Irish Famine (1845-1850) on the long-run individual decision to migrate to the US during the Age of the Mass Migration. We construct a unique dataset based on two early 20th century Irish Censuses and the Ellis Island Administrative Records. This allows us to test whether the Great Irish Famine, one of the most lethal episodes of mass starvation in history, had a long-run impact on individuals' migration decisions. Controlling for individual and geographical characteristics, we find that the Irish Famine was a significant long-run driver of individuals' migration choices.
Keywords: F22; N33; N93; 330; mass migration; negative shock; long-run impact; Great Famine